Numerical modeling of hypolimnetic oxygenation by electrolysis of water - Jacimovic, Nenad; Hosoda, Takashi; Park, Ho-Dong; Ivetic, Marko (Thermal Science, 2017)
The paper presents a novel method for hypolimnetic oxygenation by electrolysis of water. The performance of the method is investigated by the laboratory and the field experiment. The laboratory experiment is conducted in a 90 L vessel, while the field experiment is conducted at the lake Biwa in Japan. In order to provide a better insight into involved processes, a numerical model for simulation of bubble flow is developed with consideration of gas compressibility and oxygen dissolution. The model simultaneously solves 3-D volume averaged two-fluid governing equations. Developed model is firstly verified by simulation of bubble flow experiments, reported in the literature, where good qualitative agreement between measured and simulated results is observed. In the second part, the model is applied for simulation of conducted water electrolysis experiments. The model reproduced the observed oxygen concentration dynamics reasonably well.